Systematic experimental search for Fe2YZ Heusler compounds predicted by ab-initio calculation. (April 2021) - Kratochvílová, M.; Klicpera, M.; Malý, F.; Valenta, J.; Veis, M.; Colman, R.H.; Heczko, O.
Abstract: An extensive experimental investigation of Fe-based Heusler alloys has been performed in order to potentially prepare new materials which are tetragonally distorted and have large perpendicular magnetic anisotropy crucial not only for the STT-MRAM applications but also for magnetic shape memory devices. Based on criteria demanded for the MSM applications 25 Fe2 YZ various compounds were selected for the synthesis using arc melting from more than 60 systems suggested theoretically. Only four compounds Fe2 MnSn, Fe2 NiSi, Fe2 NiGe, and Fe3 Ga were homogeneous single phase. None of the studied Fe-based materials exhibited the predicted tetragonal structure. Magnetic measurements confirmed that all investigated compounds are soft ferromagnets with no sign of a structural transition. Our results contradict the ab-initio calculations showing the limits of theoretical predictions by incomplete high throughput calculations as well as the limitations of the standard synthesis techniques. Highlights: We have attempted to synthesize 25 Fe-based alloys from the list of more than 60 systems studied using DFT calculations. We were able to prepare homogeneous polycrystals of four materials – Fe3 Ga, Fe2 MnSn, Fe2 NiSi, and Fe2 NiGe by arc-melting. Except Fe2 MnSn, which is hexagonal, all compounds reveal a cubic structure, in contrast to the theoretical predictions. Measurement confirmed that Fe2 MnSn, Fe2 NiSi, Fe2 NiGe, and Fe3 Ga are soft ferromagnets with no sign of a structural transition.